16S rRNA gene sequence based identification of Vibrio spp. in shrimp and tilapia hatcheries of Bangladesh - Hasan, Md Abdur Razzak; Siddique, Mohammad Anwar; Hasan, Mahmud; Hossain, M Anwar; Rahman, Mohammad Shamsur (Dhaka University Journal of Biological Sciences, 2017)
Presence of Vibrio spp., one of the deadliest fish and shrimp pathogens in aquaculture facilities worldwide for which hatchery owners often suffer hectic economic losses, were identified in shrimp and tilapia hatcheries of Cox’s Bazar and Mymensingh, Bangladesh. Thirty seven Vibrio isolates, selected on the basis of their morphological dissimilarities in thiosulphate citrate bile salt sucrose agar (TCBS) plate, were subjected to amplified 16S ribosomal DNA restriction analysis (ARDRA) by using AluI restriction enzyme following their DNA extraction and amplification of 16S rRNA (1450 bp). From this analysis, representative isolates of 8 ARDRA groups, named as ARH 1 to ARH 8, of different band patterns were sequenced and identified as Vibrio alginolyticus, Aeromonas veronii, A. hydrophila, Vibrio vulnificus, V. cholerae, Edwardsiella hoshinae, Bacillus methylotrophicus and Aeromonas veronii, respectively. Vibrio species identified in this study are pathogenic for human and aquatic organisms, and were found only in shrimp hatchery with the dominance of V. alginolyticus. Findings of this study indicate the poor quality of water treatment and management of the hatchery. It was also observed that all the three Vibrio species were present in the Artemia rearing tank which indicates the possible source of pathogens. Dhaka Univ. J. Biol. Sci. 26(1): 45-58, 2017 (January)